Logic and religious belief - Bueno Laguna, Marino (2011)
Logic has a precise, universal language. It is possible by means of the logicallanguage to put into practice the rigor and clarity of mathematics in the languageof philosophers and theologians. In this opportunity we employ the logicallanguage in the theological language. We introduce the concepts and argumentsof Catholic religious belief formalized in modal logic.